HERITAGE OR MODERN TOURISM - Pinto, Luís M.; Carvalho, Paulo; País, Luís (European Scientific Journal, ESJ, 2015)
As referred by Umberto Eco there must be a dialog between the subject and the object. (Eco, 1989) Tourism could give a push into the maintenance of architecture quality, and preserving of architectonic historical zones. So what is the purpose of the tourism realm in the 21st century?